Optimal cell tab design and cooling strategy for cylindrical lithium-ion batteries - Li,S; Kirkaldy,N; Zhang,C; Gopalakrishnan,K; Amietszajew,T; Bravo,Diaz L; Varela,Barreras J; Shams,M; Hua,X; Patel,Y; Offer,G; Marinescu,M (Journal of Power Sources, 2021)
The ability to correctly predict the behavior of lithium ion batteries is critical for safety, performance, cost and lifetime. Particularly important for this purpose is the prediction of the internal temperature of cells, because of the positive feedback between heat generation and current distribution. In this work, a comprehensive electro-thermal model is developed for a cylindrical lithium-ion cell. The model is comprehensively parameterized and validated with experimental data for 2170 cylindrical cells (LG M50T, NMC811), including direct core temperature measurements. The validated model is used to study different cell designs and cooling approaches and their effects on the internal temperature of the cell. Increasing the number of tabs connecting the jellyroll to the base of the cylindrical-can reduces the internal thermal gradient by up to 25.41%. On its own, side cooling is more effective than base cooling at removing heat, yet both result in thermal gradients within the cell of a similar magnitude, irrespective of the number of cell tabs. The results are of immediate interest to both cell manufacturers and battery pack designers, while the modelling and parameterization framework created is an essential tool for energy storage system design.